Evaluasi Bantuan Operasional Sekolah (BOS) Dalam Peningkatan Mutu Pendidikan di SMK Kristen BM Salatiga - Setyoningsih, Ari; Ismanto, Bambang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This reseach was conducted with the aim of seeking a information about the implementation of BOS and to obtain a gap in the implementation of BOS at the BM Salatiga Christian Vocational School in improving the quality of education. This study uses an evaluation model, namely the evaluation of gap in the implementation of a program. The subjects in this study were the principal, BOS treasurers, parents and students. Data collection techniques used were observation, interviews and documentation and later analyzed using the Miles and Hubermen model which included data reduction, presentation and then drawing conclusions. Based on the results of the study, it shows that there is still a gap between the implementation and the BOS standards at BM Salatiga Christian Vocational School. At the design stage, the implementation of BOS is in accordance with the BOS 2020 Technical Guidelines. At the installation stage there are still gaps, including when there is an urgent expenditure and while the expenditure must be based on the SPJ. At the stage of the process, There were also gaps, including the delay in disbursement of fuds, where BOS was the main source in implementing learning in schools so that it could be concluded that there was still a gap between the implementation of BOS and the Technical Guidelines.